Anesthetic Drug Discovery and Development: A Case Study of Novel Etomidate Analogs - McGrath, Megan (Methods Enzymol, 2018)
All currently available general anesthetic agents possess potentially lethal side effects requiring their administration by highly trained clinicians. Among these agents is etomidate, a highly potent imidazole-based intravenous sedative-hypnotic that deleteriously suppresses the synthesis of adrenocortical steroids in a manner that is both potent and persistent. We developed two distinct strategies to design etomidate analogs that retain etomidate’s potent hypnotic activity, but produce less adrenocortical suppression than etomidate. One strategy seeks to reduce binding to 11β-hydroxylase, a critical enzyme in the steroid biosynthetic pathway, which is potently inhibited by etomidate. The other strategy seeks to reduce the duration of adrenocortical suppression after etomidate administration by modifying the drug’s structure to render it susceptible to rapid metabolism by esterases. In this chapter, we describe the methods used to evaluate the hypnotic and adrenocortical inhibitory potencies of two lead compounds designed using the aforementioned strategies. Our purpose is to provide a case study for the development of novel analogs of existing drugs with reduced side effects.